(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
In the present study sustained release diclofenac sodium matrix tablets were prepared using Kollidon SR polymer. Hydroxypropyl methylcellulose (HPMC 15 cps) and poly ethylene glycol (PEG-600) polymers respectively were used in formulating tablets prepared by direct compression and wet granulation methods. The polymers were used to explore the release pattern of the drug into the dissolution media. The tablets were also prepared in various shapes (caplet oval, round oval and flat oval). A comparatively higher release rate of drug was obtained from the polymer HPMC 15 cps at 10% concentration for directly compressed matrix tablet than those containing 20% of HPMC after a definite period of time. In wet granulation process, 10% PEG-600 containing tablets showed a better release than those containing 20% PEG. The drug release was also found to be sustained in case of wet granulation method than that of the direct compression method. Again the caplet shaped tablets in case of direct compression method showed better release rate of drug than those of the round oval and flat oval shaped tablets. Thus the result of this study shows that the proper selection of the percentage of polymer and the suitable shape of tablet and proper manufacturing method can provide a greater opportunity in designing sustained release dosage forms. Key words: Matrix tablet; release pattern; direct compression; wet granulation; PEG 600; Kollidon SR. DOI: 10.3329/sjps.v2i2.5828 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 76-80